Progress and Challenges Connected with the Integration of Renewable Energy Sources with Railway Distribution Networks - Valeriy Kuznetsov; Petro Hubskyi; Artur Rojek; Magdalena Udzik; Krzysztof Lowczowski (Energies, 2024)
Rail is the most efficient and low carbon means of transport, but efforts are still being made to improve the energy efficiency of this sector. In Poland, one of the elements of the implementation of the energy transformation in rail is the “Green Railway” program, which assumes an increase in the share of renewable energy sources (RES) in the power supply structure of the sector to 50% in 2025 and 85% in 2030, and ultimately, to 100%. An increase in energy efficiency leads to a reduction in financial costs, and also contributes to improving the environment and, consequently, to enhancing the economic and social benefit through a cost–benefit analysis. Energy consumption in railway operations is characterized (unlike in construction) by being repetitive. This energy consumption is produced in four areas: in the movement of trains; in auxiliary systems in the trains; in auxiliary systems in the infrastructure (lighting consumption of tunnels or sections of track, point heating systems, the signaling and communication systems, etc.); and in stations, workshops and by other consumers. The aim of this article was to review modern technologies using renewable energy sources in rail transport for traction and non-traction customers.